Practice of Early Childhood Developmental Milestone Assessment and Its Determinants Among Health Professionals Working at Public Hospitals in Addis Ababa, Ethiopia: A Cross-Sectional Study - Tesfay H; Sebsibe G; Tesfaye T (Dove Medical Press, 2021)
Haileslassie Tesfay,1 Girum Sebsibe,2 Tewodros Tesfaye2 1College of Medicine and Health Sciences, Debre Birhan University, Debre Birhan, Ethiopia; 2Department of Nursing, School of Nursing and Midwifery, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Tewodros TesfayeDepartment of Nursing, School of Nursing and Midwifery, Addis Ababa University, PO Box 4412, Addis Ababa, EthiopiaTel +251 913 69 80 81Email teddykera@gmail.comBackground: Early childhood developmental assessment refers to the continual process of observing, gathering, recording, and interpreting information to make developmental and instructional decisions and measure young children's performance over time. Significant changes in the physical and neuropsychomotor developmental milestones take place in the first 2 years of life. Children younger than 3 years of age (36 months) who are at risk of having developmental delays may be eligible for early intervention treatment services. The study aimed to assess practice in early childhood developmental assessment and its determinants among health professionals working in public hospitals in Addis Ababa, Ethiopia.Methods: This facility-based descriptive cross-sectional study was conducted from September to April 2018, with a total sample size of 268 health professionals from six public hospitals in Addis Ababa, Ethiopia. The data were entered into EpiData software version 4.2, and analyzed by SPSS version 23 software for bivariate and multivariable logistic regression analysis. Significant associations were taken as p< 0.05 and the strength of associations was expressed using odds ratios.Results: The practice of early childhood developmental milestone assessment was found to be 27.8%. Being a general practitioner (AOR=23.826, 95% CI: 6.77- 83.9, p=0.000) or health officer (AOR=11.02, 95% CI: 2.1- 58.812, p=0.005), and work experience greater than 11 years (AOR=20.897, 95% CI: 1.5- 291.49, p=0.024) were significantly associated with good practice of early childhood developmental milestone assessment.Conclusion: Practice of early childhood developmental milestone assessment remains poor. Training and sharing experiences among different professions, and assigning professionals with the highest levels of work experience in the service could improve the practice levels.Keywords: early childhood, developmental milestone assessment, practice